The Experience Is (Not) Everything: Sequential Outcomes and Social Decision-Making - Johannes Buckenmaier; Eugen Dimant (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In multiple pre-registered experiments, we examine the effect of sequences of positive and negative experiences on altruism, trust, trustworthiness, and cooperation. For non-social experiences, we find no effect on subsequent behavior in any of these social domains. However, when experiences are social in nature, we find more cooperation after gains than after losses. For neutral experiences with gains equalizing losses, we find no evidence for a differential effect of experiences irrespective of whether the experience is social or not. Our findings are in line with recent evidence on decision making under risk, showing that the effect of prior experiences depends on task similarity. Beyond that, we extend these findings to various forms of social decision making. Our results suggest that the overall valence of an experience (gain or loss) matters, whereas its dynamic trend (improving or deteriorating) does not.
Keywords: C72; C91; D80; D90; 330; altruism; cooperativeness; sequential decisions; trust